2018
DOI: 10.2298/vsp151118357r
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and spiritual well-being aspects of the quality of life in colostomy patients

Abstract: Background/Aim. Colorectal cancer and its treatment can have a negative impact on the quality of life which has become an important outcome measure for cancer patients. The aim of this work was assessment of psychological and spiritual dimension of the quality of life in colostomy patients, regarding the gender and age. Methods. This is a cross-sectional study conducted at the Abdominal Surgery Polyclinic in the Clinical Canter of Vojvodina among colostomy patients operated between January 2010 and June 2011. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Of the 37 studies, 1 targeted patients aged 60 or above [ 36 ], 1 targeted patients whose age was 80 or over [ 33 ], and the remaining 35 targeted patients aged from 19 to 88. Furthermore, 7 studies focused on patients with ostomy [ 27 , 30 , 34 , 40 , 44 , 45 , 46 ], and the remaining 30 focused on patients with or without ostomy, or they did not mention whether the patients had an ostomy. The topics examined with a statistical analysis in terms of gender differences were divided into three aspects: psychological outcomes, social outcomes, and coping strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 37 studies, 1 targeted patients aged 60 or above [ 36 ], 1 targeted patients whose age was 80 or over [ 33 ], and the remaining 35 targeted patients aged from 19 to 88. Furthermore, 7 studies focused on patients with ostomy [ 27 , 30 , 34 , 40 , 44 , 45 , 46 ], and the remaining 30 focused on patients with or without ostomy, or they did not mention whether the patients had an ostomy. The topics examined with a statistical analysis in terms of gender differences were divided into three aspects: psychological outcomes, social outcomes, and coping strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Dunn et al speculated that male patients were less likely to seek health services and that young, poor males needed specific support [ 31 ], while Mols et al did not discuss this point [ 11 ]. In addition, there were also 19 studies stating that no gender difference existed in anxiety, depression, body image distress, distress, emotional functioning/well-being, psychological health, or spiritual well-being [ 12 , 20 , 21 , 22 , 24 , 25 , 29 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 49 , 50 , 51 , 52 ]. Specifically, of the 19 studies, 14 utilized QOL-related tools to measure patients’ psychological outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Ainda assim, é necessário fornecer suporte sob medida, a fim de prevenir e minimizar respostas negativas. (23) Apesar disso, o medo de eventos constrangedores limita a dimensão social e comunitária da prática religiosa como a participação em momentos litúrgicos e a inserção em trabalhos pastorais passando a desenvolver a dimensão individual religiosa.…”
Section: Discussionunclassified
“…It is believed to be helpful for individuals to overcome difficulties in life, provide life experiences, and contribute to their well being. The study conducted by Repic et al (2018) revealed the importance of the spiritual aspect of quality of life among patients with colostomy. Dimensions related to religious rituals were found to be important for participants.…”
Section: Introductionmentioning
confidence: 99%